Petrogenesis of Late Cretaceous I-type granites in the southern Yidun Terrane: New constraints on the Late Mesozoic tectonic evolution of the eastern Tibetan Plateau - Wang, Xin-Song; Hu, Rui-Zhong; Bi, Xian-Wu; Leng, Cheng-Biao; Pan, Li-Chuan; Zhu, Jing-Jing; Chen, You-Wei (Lithos, 2014)
The collision between the Lhasa and Qiangtang terranes, prior to the Indo–Asian collision, is a critical aspect in terms of development of the Tibetan Plateau. It has been demonstrated that the occurrence of the Late Cretaceous granites (110–80Ma) in the Yidun Terrane, eastern Tibetan Plateau (ETP) associates with the Lhasa–Qiangtang collision. The Xiuwacu Late Cretaceous pluton in the southern Yidun Terrane, consists three phases including biotite granitic porphyry (phase 1), monzogranite (phase 2), and alkali–feldspar leucogranite (phase 3), which have zircon U–Pb ages ranging from 85.5Ma to 84.4Ma. All these three phases are metaluminous or slightly peraluminous granites (A/CNK=0.96–1.07), with high SiO2 (70.0–76.0wt.%), K2O+Na2O (7.5–10.7wt.%), and Ga/Al (2.5–4.7), and relatively low CaO (0.39–1.67wt.%), MgO (0.01–0.57wt.%), and P2O5 (0.01–0.17wt.%). The granites are enriched in light rare earth elements (LREEs), Rb, Th, U and Ta, but depleted in heavy REEs (HREEs), Ba, Sr, P, and Ti, with significantly negative Eu anomalies (Eu/Eu*=0.24–0.59). Comparing to classic A-type granites, these samples present higher Sr (10.1–256ppm, mostly >100ppm) and lower FeO*/MgO ratios (1.2–9.9) and Zr+Nb+Ce+Y (248–483ppm, mostly <350ppm). However, they show highly fractionated I-type granites affinities. All these phases have relatively high (87Sr/86Sr)i (0.7075–0.7098), negative εNd(t) (−8.0 to −6.9) and εHf(t) (−7.6 to −3.2) values, and ancient Nd and Hf model ages (1.7–1.3Ga), which indicates similar origins predominately through partial melting of ancient mafic-intermediate lower continental crust. Besides, variable zircon δ18O values (5.9‰ to 8.4‰, partly<6.5‰) and the occurrences of mafic microgranular enclaves (MMEs) within the granites probably indicate a contribution of mantle components. Although the Xiuwacu Late Cretaceous intrusions show higher SiO2 values and lower Sr/Y ratios comparing to other three high Sr/Y I-type intrusions (Relin, Hongshan, and Tongchanggou) in the southern Yidun Terrane, similar (87Sr/86Sr)i, εNd(t), εHf(t), and δ18O contents in all of these four intrusions point to a common source. We propose that both the Xiuwacu intrusions and the other three intrusions in the southern Yidun Terrane were generated under a late- or post-collision environment related to the Lhasa–Qiangtang collision during the Late Cretaceous. Decompression induced upwelling of mantle-derived magmas to underplate and provided heat for the anatexis of thickened lower crust. Then, those Late Cretaceous magmas were brought into the southern Yidun Terrane by mixing of lower continental crust-derived melts and minor mantle-derived magmas, and the following fractional crystallization. Occurrence of these late- or post-collision magmas probably indicates that the timing of both the Lhasa–Qiangtang collision and the eastern Tibetan Plateau uplifting was earlier than the Late Cretaceous, and that the Lhasa–Qiangtang collision did not cease at least until ca. 80Ma. Afterwards, tectonic setting of the eastern Tibetan Plateau was progressively to be under a control mainly of the subduction of the Neo-Tethys Ocean and subsequent Indo–Asian collision. •The Xiuwacu Late Cretaceous intrusions are felsic I-type granites.•Mixing of thickened lower crust- and mantle-derived melts produce the four intrusions.•They were generated under a post- or late-collisional tectonic setting.•Lhasa–Qiangtang collision and East Tibetan Plateau uplifting occurred earlier than the Late Cretaceous.